Unveiling the state of the art: a systematic review and meta-analysis of paper-based microfluidic devices - García-Azuma, Rodrigo; Werner, Karen; Revilla-Monsalve, Cristina; Trinidad, Oscar; Altamirano-Bustamante, Nelly F.; Altamirano-Bustamante, Myriam M. (Frontiers in Bioengineering and Biotechnology, 2024)
This systematic review and meta-analysis present a comprehensive evaluation of paperbased microfluidic devices, focusing on their applications in immunoassays. These devices are emerging as innovative solutions to democratize access to diagnostic technologies, especially in resource-limited settings. Our review consolidates findings from diverse studies to outline advancements in paper-based microfluidic technology, including design intricacies and operational efficacy. Key advantages such as low cost, portability, and ease of use are highlighted alongside a critical analysis of performance metrics, including sensitivity and specificity. The review also addresses challenges, such as the need for further validation and optimization for broader clinical applications. Notable findings include the categorization of literature based on the design and operational nuances of these diagnostic tools, exploration of various methodologies, fabrication techniques, detection methods, and applications, especially in protein science. Our meta-analysis extends to the diverse applications of these technologies, providing a framework for classifying and stratifying their uses in diagnostics. We conclude with a critical discussion on the validation processes, including cross-validation and rigorous control testing, essential for ensuring the robustness of microfluidic devices. This study offers novel insights into the computational strategies underpinning these technologies and serves as a comprehensive roadmap for future research, potentially broadening the impact across the protein science universe.